2020
DOI: 10.18632/aging.102985
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of verbenalin-treated human amniotic epithelial cells reveals therapeutic potential for Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) has become a major world health problem as the population ages. There is still no available treatment that can stop or reverse the progression of AD. Human amnion epithelial cells (hAECs), an alternative source for stem cells, have shown neuroprotective and neurorestorative potentials when transplanted in vivo. Besides, studies have suggested that stem cell priming with plant-derived bioactive compounds can enhance stem cell proliferation and differentiation and improve the disease-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…Furthermore, hAECs treated with vitamin C showed increased survival after transplantation and secreted a greater amount of growth factors, which improved the therapeutic potential of hAECs in mice with POF [ 124 ]. The plant-derived bioactive compound verbenalin significantly increased gene expression in hAECs, contributing to the enhanced neural repair potential of hAECs for AD [ 125 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, hAECs treated with vitamin C showed increased survival after transplantation and secreted a greater amount of growth factors, which improved the therapeutic potential of hAECs in mice with POF [ 124 ]. The plant-derived bioactive compound verbenalin significantly increased gene expression in hAECs, contributing to the enhanced neural repair potential of hAECs for AD [ 125 ].…”
Section: Methodsmentioning
confidence: 99%
“…Natural compounds with proven bioactivities can control cellular behavior and early biological and molecular events to direct the targeted differentiation of stem cells in a lineage-specific manner. Only a handful of studies were conducted to evaluate the effects of naturally occurring compounds on hAECs ( Ferdousi et al, 2019 , 2020 ; Hou et al, 2020 ). Furthermore, while current researches focus on the safety and efficacy of translating hAEC therapy into clinical practices ( Murphy et al, 2010 ; Strom et al, 2013 ; Lim et al, 2017 , 2018 ; Srinivasan et al, 2020 ), priming approaches using natural bioactive compounds to improve its effectiveness has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the fact that hAECs were discovered decades ago, few researches have been done on using natural compounds to optimize the microenvironment or to regulate the early biological events for controlled differentiation of hAECs. In our previous studies, we have reported that a natural compound rosmarinic acid could induce neuronal differentiation in hAEC (Ferdousi et al, 2019), whereas verbenalin-treated hAECs showed therapeutic potential for Alzheimer's disease (Ferdousi et al, 2020). Another recent study has reported that vitamin C, a natural antioxidant, could promote the proliferation, migration, and self-renewal of hAECs in vitro and elevate the therapeutic potential of hAECs in premature ovarian insufficiency model mice (Hou et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…The procedure of cell isolation and cell culture have been explained elsewhere in detail ( Ferdousi et al, 2019 , 2020 ; Furuya et al, 2019 ). Briefly, hAESCs were obtained from the term placenta donated by mothers who underwent cesarean delivery.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, hAESCs cultured in a 3D microenvironment as spheroids, have highly expressed the stemness-related genes compared to their 2D counterpart as well as compared to iPSCs and MSCs ( Ferdousi et al, 2019 ). We have previously investigated the gene expression profiles of several natural compounds in hAESCs ( Ferdousi et al, 2019 , 2020 ) in an effort to screen eligible natural compounds for further in-depth investigations. Among the compounds that we have screened in hAESCs, isorhamnetin (ISO) exerts cardiac morphogenesis, and antifibrotic potential.…”
Section: Introductionmentioning
confidence: 99%